Cell death induced autophagy contributes to terminal differentiation of skin and skin appendages. Issue 5 (3rd May 2020) - Koenig, Ulrich; Robenek, Horst; Barresi, Caterina; Brandstetter, Marlene; Resch, Guenter P.; Gröger, Marion; Pap, Thomas; Hartmann, Christine
ABSTRACT: In the adult mammalian skin, cells are constantly renewing, differentiating and moving upward, to finally die in a yet not fully understood manner. Here, we provide evidence that macroautophagy/autophagy has a dual role in the skin. In addition to its known catabolic protective role as an evolutionary conserved upstream regulator of lysosomal degradation, we show that autophagy induced cell death (CDA) occurs in epithelial lineage-derived organs, such as the inter-follicular epidermis, the sebaceous- and the Harderian gland. By utilizing GFP-LC3 transgenic and ATG7-deficient mice, we show that CDA is initiated during terminal differentiation at a stage when the cells have become highly resistant to apoptosis. In these transitional cells, the Golgi compartment expands, which accounts for the formation of primary lysosomes, and the nucleus starts to condense. During CDA a burst of autophagosome formation is observed, first the endoplasmic reticulum (ER) is phagocytosed followed by autophagy of the nucleus. By this selective form of cell death, most of the cytoplasmic organelles are degraded, but structural proteins remain intact. In the absence of autophagy, consequently, parts of the ER, ribosomes, and chromatin remain. A burst of autophagy was stochastically observed in single cells of the epidermis and collectively in larger areas of ductal cells, arguing for a coordinated induction. We conclude that autophagy is an integral part of cell death in keratinocyte lineage cells and participates in their terminal cell fate. Abbreviations: Atg7: autophagy related 7; BECN1: beclin 1; CDA: cell death-induced autophagy; Cre: Cre-recombinase; DAPI: 4′, 6-diamidino-2-phenylindole; ER: endoplasmatic reticulum; GFP: green fluorescent protein; HaGl: haderian gland; IVL: involucrin; KRT14: keratin 14; LD: lipid droplet; LSM: laser scanning microscope; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; PN: perinuclear space; RB: residual body; rER: rough endoplasmatic reticulum; SB: sebum; SG-SC: stratum granulosum – stratum corneum; SGl: sebaceous gland; SQSTM1: sequestosome 1; TEM: transmission electron microscopy; TUNEL: terminal deoxynucleotidyl transferase dUTP nick end labelling.